2023
DOI: 10.5812/ijcm-131622
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Benson Relaxation Technique on Caregiver Burden in the Informal Caregivers of Cancer Patients: A Randomized Controlled Trial

Abstract: Background: Informal caregivers provide long-term support and care for cancer patients and they do not receive enough support from the family and the health system; as a result, they suffer from a lot of caregiver burden. Objectives: In the current study, we investigated the effect of the Benson relaxation technique on caregiver burden in informal caregivers of cancer patients. Methods: This randomized clinical trial with a control group was conducted on 113 caregivers, who scored X ≥ 48 from the Novak and Gue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In the IG, we designed a combined intervention using self-determination theory (SDT) and the BRT, which were used separately in previous studies, and successfully reduced the severity of the caregiving burden among caregivers [17,26]. There will be six sessions over six months, where each session will be conducted at the beginning of each month.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the IG, we designed a combined intervention using self-determination theory (SDT) and the BRT, which were used separately in previous studies, and successfully reduced the severity of the caregiving burden among caregivers [17,26]. There will be six sessions over six months, where each session will be conducted at the beginning of each month.…”
Section: Interventionmentioning
confidence: 99%
“…These techniques include mindfulness exercises that specifically treat a variety of mental and emotional symptoms such as burden, anxiety, pain, depression, mood swings, and self-esteem. Related studies have demonstrated that BRT is more effective in reducing caregiving burden, anxiety, and depression in various populations, including among caregivers [17,18].…”
Section: Introductionmentioning
confidence: 99%